2011
DOI: 10.1016/j.jdeveco.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Sectoral differentiation, allocation of talent, and financial development

Abstract: I present a theory of development in which heterogeneously talented entrepreneurs require credit to start new projects and open new sectors. During development the variety of sectors expands, which allows better sorting of entrepreneurial talent. The paper shows that, in addition to increasing the average productivity of matches between agents and sectors, this process also mitigates informational frictions in the …nancial markets. Furthermore, the impact of sectoral variety on the operation of …nancial market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Second, the competitive screening framework of this paper shares many features with the occupational choice models by Grüner (2003), Jaimovich (2011), Inci (2013), and Spiganti (2020b, 1 where heterogeneous agents must choose between entrepreneurship and an outside option. Similarly to this paper, the contractual structure of the credit market introduces endogenous wealth classes, which receives different credit contracts.…”
Section: Related Literaturementioning
confidence: 98%
“…Second, the competitive screening framework of this paper shares many features with the occupational choice models by Grüner (2003), Jaimovich (2011), Inci (2013), and Spiganti (2020b, 1 where heterogeneous agents must choose between entrepreneurship and an outside option. Similarly to this paper, the contractual structure of the credit market introduces endogenous wealth classes, which receives different credit contracts.…”
Section: Related Literaturementioning
confidence: 98%
“…Alonso-Carrera and Raurich (2010) showed that differences in sectors' structure, together with production factors endowment can influence achieving different economic growth rates. Jaimovich (2011) proposed a model where it is shown that differentiation of sectors, along with operation of financial markets can shape the patterns of development. According to Gilchrist et al (1995) regional industrial diversification policies have positive roles in growth of economic welfare.…”
Section: Introductionmentioning
confidence: 99%
“…Economic sectors (Jaimovich, 2011;Halkos, Tzeremes, 2008;Tanuwidjaja, Thangavelu, 2007;Sonobe et. al., 2004;, production (Bond et al, 2010;Sarkar, 2007;Briec, Cavaignac, 2007;Kosempel, 2004;Tvaronaviciene, Lankauskiene, 2013) and other different factors determining the development of economic sectors (e.g.…”
Section: Introductionmentioning
confidence: 99%